Behavioral Problems Among Secondary School Students from the Perspective of Their Teachers in Bani Walid - Dr. Lutfiya Saeed Albggar; Dr. Nuri Salih Mahmud (Journal of Scientific and Human Dimensions, 2025)
The current study aimed to identify the behavioral problems of secondary school students from the point of view of their teachers in the city of Bani Walid. For this purpose, the researchers used the descriptive approach and selected the sample intentionally from secondary schools located in the scope of Al-Dhahra and Bani Walid Center, and their number reached (80) male and female teachers. In order to achieve the objectives of the study, the researchers then built the study tool after reviewing some previous studies related to the subject of the study, where the study tool consisted of (24) paragraphs. This tool was distributed to secondary schools located in the scope of Al-Dhahra and Bani Walid Center, in the city of Bani Walid, and their number reached (5) schools out of (6) secondary schools. The researchers conducted the validity and reliability of the study tool, and its reliability rate reached (680). Among the most important results reached by the study are: The most widespread behavioral problems among the study sample from the point of view of secondary school teachers on the questionnaire as a whole in terms of percentages are paragraph No. (8) with a percentage of (95%) and it states the density of the number of students inside the classroom, paragraph No. (11) with a percentage of (86.25%) and it states running away from school before the end of the school day, paragraph No. (17) with a percentage of (7875%) and it states the lack of cooperation of parents in solving their children’s problems, or paragraph No. (24) with a percentage of (72.5%) and it states the abundance of writing on the school walls, and paragraph No. (1) with a percentage of (661.25) and it states the lack of discipline outside the classroom, especially in the school yard, and as for the paragraphs that were low in terms of extracting percentages, they are paragraph (6) with a percentage of (48.75%) and it states that the behavior is practiced without calculating the results and paragraph No. (21) with a percentage of (41.25%) and states: “Note: Paragraph No. (13) with a percentage of (37.5%) states, “Hitting colleagues during class,” Paragraph No. (9) with a percentage of (35%) states, “He defends his friends even if they are wrong,” and Paragraph No. (4) with a percentage of (31.25%) states, “He constantly repeats his mistakes due to his lack of concentration.” In light of the results of the study, it was stated that